On the Convective Motions in Different Layers of Atmosphere - Gvelesiani, Anzor I. (Journals of Georgian Geophysical Society, 2017)
From the unified point of view, this paper gives some known and new results of theoretical and experimental investigations of slow mesoscale convective motions in the neutral and conductive atmosphere. Specific thermo-hydrodynamic regime conditions of the considered mediums were taken into account for determination of onset of convection and the vertical velocity of arisen heat thermal. Carried out original analytical and numerical investigations showed that largescale eddy regions and zones of divergence and convergence responsible to existence of three-dimensional motions of air in the neutral atmosphere and in the ionosphere.